Implementasi Algoritma Genetika Untuk Penjadwalan Ujian Pada Universitas Handayani Makassar - Syahrul Saleh; Najirah Umar; M Adnan Nur (Ikatan Ahli Informatika Indonesia, 2023)
This research relates to Handayani University Makassar formerly STMIK Handayani Makassar. The university offers various programs in the field of computer science and IT management. One of the main problems faced is that the preparation of the exam schedule is currently still done manually using Microsoft Excel, prone to errors and time consuming. This research aims to develop an automated system for preparing exam schedules using genetic algorithms. Genetic algorithm is a computer method that helps find optimal solutions in exam scheduling. The results of this study are expected to help improve the efficiency and accuracy of the preparation of the exam schedule at Handayani University Makassar.